Efektivitas Layanan Konseling Kelompok Terhadap Peningkatan Konsep Diri Positif Peserta Didik - Junie Krisna Mendrofa; Hosianna Rodearni Damanik; Mondang Munthe; Justin Foera-era Lase (Conseils : Jurnal Bimbingan dan Konseling Islam, 2024)
The aim of this study is to find out how effective group counselling services are in improving the positive self-concept of learners. The study uses a quantitative approach with experimental quasy design. Data collection is carried out through the dissemination of test instruments, interviews and observations in the classroom as the teaching learning process takes place. The test sample used the experimental class X-OTKP and the Control Class X-TKJ. The data analysis technique used in this study using the N-Gain test was carried out by calculating the difference between the pre-test (before treatment) and post-test values. (sesudah diberi perlakuan). From the instrumental results, interviews and observations show that there is a positive self-concept enhancement for the pupils. Out of the 20th pre-test of students in the X-OTKP class (experiment) there were 7 students who belonged to low self-concept and set as subject of treatment. The implementation of group counselling services for 4 (four) times, with the topic of discussion of improvement of positive self-concept of the students, showed that there was improvement in positive self -concept for the students. Then the application of group counseling services can be said to be effective. So this study shows that group counselling services are effective in improving positive self-conceptions of pupils.